Spatial Frequencies Used in Landolt C Orientation Judgments: Relation to Inferred Magnocellular and Parvocellular Pathways - McAnany, J. Jason (2008)
The purpose of this study was to define the spatial frequencies that underlie judgments of Landolt C orientation under test conditions designed to favor either the magnocellular (MC) or parvocellular (PC) pathway. Contrast thresholds of two observers were measured for briefly presented Landolt Cs of four sizes, using steady- and pulsed-pedestal paradigms to bias performance toward the MC and PC pathways, respectively. Contrast thresholds were derived from a two-alternative forced-choice orientation judgment task using the QUEST procedure. The Landolt Cs were either low-pass or high-pass Gaussian filtered with a range of cut-off object spatial frequencies (cycles per letter) to limit their frequency content. Center object frequencies were derived from plots of log contrast threshold for orientation judgments vs. log filter cutoff object frequency. The function relating center object frequency to Landolt C angular subtense was nonlinear on log-log coordinates for both the steady- and pulsed-pedestal paradigms, indicating that different object frequencies were used to judge Landolt C orientation at different optotype sizes. However, the function was substantially steeper under the pulsed-pedestal than under the steady-pedestal paradigm, such that a large change in optotype size produced a relatively small change in retinal spatial frequency (cycles per degree). The pattern of results is consistent with previously reported differences between the spatial contrast sensitivity functions of the inferred MC and PC pathways.